Workplace Sexual Harassment 30 Years on: A Review of the Literature - McDonald, Paula (International Journal of Management Reviews, 2012)
Despite its proscription in legal jurisdictions around the world, workplace sexual harassment (SH) continues to be experienced by many women and some men in a variety of organizational settings. The aims of this review article are threefold: first, with a focus on workplace SH as it pertains to management and organizations, to synthesize the accumulated state of knowledge in the field; second, to evaluate this evidence, highlighting competing perspectives; and third, to canvass areas in need of further investigation. Variously ascribed through individual (psychological or legal consciousness) frameworks, sociocultural explanations and organizational perspectives, research consistently demonstrates that, like other forms of sexual violence, individuals who experience workplace SH suffer significant psychological, health- and job-related consequences. Yet they often do not make formal complaints through internal organizational procedures or to outside bodies. Laws, structural reforms and policy initiatives have had some success in raising awareness of the problem and have shaped rules and norms in the employment context. However, there is an imperative to target further workplace actions to effectively prevent and respond to SH.
Keywords: Bibliographie; Nettoyer